2001
DOI: 10.1111/0022-4537.00224
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Concept of a Migrant Personality

Abstract: In this article we argue that individuals who want to emigrate possess a syndrome of personality characteristics that differentiates them from those who want to stay in their country of origin. Based on our own research, as well as other research findings, we show that those who want to resettle in another country tend to be more work-oriented and to have higher achievement and power motivation, but lower affiliation motivation and family centrality, than those who do not want to leave their country of origin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
155
0
34

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(197 citation statements)
references
References 27 publications
8
155
0
34
Order By: Relevance
“…For example, the psychoanalytic approach to studying immigrants' experience (Elovitz & Kahn, 1997) and their motivation (Marlin, 1997) might lead researchers to utilize projective methods in their studies (Fass, 2003). Another approach aimed to apply McClelland's three-motive model of human motivation (based on the motives for achievement, power, and affiliation) to the situation of international migration (Boneva & Frieze, 2001;Frieze et al, 2004). These studies demonstrated using psychological scales and survey methodology that people who are willing to emigrate possess higher levels of achievement and power motivation and lower levels of affiliation motivation in comparison to those who decide to stay in their home country.…”
Section: Motivation To Move Abroad: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the psychoanalytic approach to studying immigrants' experience (Elovitz & Kahn, 1997) and their motivation (Marlin, 1997) might lead researchers to utilize projective methods in their studies (Fass, 2003). Another approach aimed to apply McClelland's three-motive model of human motivation (based on the motives for achievement, power, and affiliation) to the situation of international migration (Boneva & Frieze, 2001;Frieze et al, 2004). These studies demonstrated using psychological scales and survey methodology that people who are willing to emigrate possess higher levels of achievement and power motivation and lower levels of affiliation motivation in comparison to those who decide to stay in their home country.…”
Section: Motivation To Move Abroad: State Of the Artmentioning
confidence: 99%
“…Boneva, Frieze, and their colleagues (Boneva & Frieze, 2001;Boneva et al, 1998;Frieze et al, 2004), for example, considered values, such as work or family orientation, together with dispositional motives, to be key determinants of the decision to move abroad. In particular, they found that emigrants score higher on work orientation and lower on family orientation in comparison to those who stay.…”
Section: Motivation To Move Abroad: State Of the Artmentioning
confidence: 99%
“…That includes, for example brain drain from developing nations, whether in the Caribbean (Tidrick, 1971) or within Eastern Europe (Boneva & Frieze, 2001). In development organizations at present, there is much interest in what is termed the "migration-development nexus."…”
Section: Brain Drainmentioning
confidence: 99%
“…Valja reći i da su migracije važna sastavnica demografskoga, ali i ukupnoga razvoja svakoga društva. Istraživa-nja Boneve i Frieze (2001) pokazala su da su osobe koje imaju želju za odlaskom u neku drugu zemlju više orijentirane na posao, postižu veće uspjehe, ali su slabije povezane s društvom i obitelji. Važan teorijski i metodološki okvir za analizu migracija kroz motive, osobne ciljeve, vrijednosti i težnje pojedinaca donijeli su u svojim znanstvenim radovima Gans (1999) i Massey (1999), a do sličnih zaključaka došli su i Koikkalainen i Kyle (2016) nedavnim empirijskim istraživanjem kognitivnih migracija koje prethode svakom stvarnom fizič-kom pokretanju i imaju veliki utjecaj na migracijsko ponašanje pojedinaca.…”
Section: Introductionunclassified
“…It is important to note that migration is an important part of both demographic and overall development of every society. The research done by Boneva and Frieze (2001) showed that people with the desire to relocate to another country were more work-oriented, achieved greater success, but had weaker ties to their family and society. Gans (1999) and Massey (1999) set up an important theoretical and methodological framework for migration analysis using motives, personal goals, values, and aspirations of individuals.…”
Section: Introductionmentioning
confidence: 99%